Analyzing Listed Indonesian Securities Companies’ Performance Using Data Envelopment Analysis - Soewignyo, Tonny (JBE (Journal of Business and Economics); Volume 9 No.1, 2010 JBE UNKLAB, 2010)
This study attempts to investigate the sensitivity of Data Envelopment Analysis (DEA) relative efficiencies to various inputs and output variable combinations measured for the year 2008 of the eight securities companies listed in Indonesia Stock Exchange (IDX), modeling performance measurement and to benchmark the efficient companies against the non-efficient companies. The results suggest that  PT. HD Capital Tbk, PT. Panin Sekuritas Tbk and PT. Trimegah Securities Tbk are 100% efficient in both global technical efficiency and pure technical efficiency amid the enduring global financial crisis.   The features of efficient peer companies make them very useful as role models that inefficient companies can emulate to improve their performance.